ICT-based Elementary School in Indonesia: Curriculum Content, Strategies, and Challenges - Atin Kurniawati; Mia Febriana; Rini Anggrainingsih (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
Along with the rapid growth of ICT, many schools offer ICT-based courses or programs. This study aimed to investigate the implementation of ICT-based elementary school in Indonesia focusing on the curriculum content, the strategies for integrating ICT curriculum into national curriculum, and the challenges they faced in running the school. Taking the case at SD ICT Al Abidin Surakarta, Indonesia, this study employed a descriptive qualitative method by conducting interview, observation, and document analysis. The result showed that the ICT curriculum included coding as the main skill by using several applications namely Code.org, Scratch Jr., Kodular, and Tinkercad.com. There were also several supporting skills taught namely rapid typing, hardware knowledge, basic Microsoft Office, graphic design, and ICT unplugged. They arranged the national curriculum content first and then added ICT content into daily learning activities. The challenges in running ICT school include the difficulty in convincing parents about the benefits of learning ICT skills, the absence of ICT school as a model in Indonesian context, and the limitedness of ICT teachers in the school. To solve it, they regularly conducted socialization to parents about ICT through seminar and social media campaign. The limitedness of ICT teachers was solved by providing regular training for class teachers to learn about ICT so they could teach ICT as well whenever needed. This study implies that ICT skills can be taught since early age and it can be integrated to formal education. For that purpose, it requires adequate learning facilities, skilled teachers, and mutual coordination with parents.